Paints And Varnishes - Corrosion Protection Of Steel Structures By Protective Paint Systems Part 3. Design Considerations BSI 1998
Paints, Varnishes, Protective coatings, Corrosion protection, Steels, Structural steels, Structures, Design, Surfaces, Sealing processes, Edge, Bolted joints, Welded joints, Components, Notches, Stiffeners, Galvanizing, Materials handling, Access, Dimensional space requirements, Length, Holes, Dimensions, Drainage, Surface texture